Slow Release Granular Biosilica Fertilizer for Peatland Oil Palm Cultivation - Luis Ibanez; Jannati, Mayada (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2025)
Indonesia’s tropical peatlands, covering over 14.9 million hectares, are critical for palm oil production but face severeagronomic constraints due to extreme acidity (pH 3.0–4.5), high water retention, low nutrient availability, and poor cation exchange capacity (CEC < 20 cmol(+)/kg). This study develops a slow-release granular biofertilizer tailored for oil palm grown in peat soils. The formulation integrates biosilica derived from calcined empty fruit bunch (EFB) ash, palm biochar, nutrient-rich fermented oil palm biomass, andAzotobacter sp. Biosilica was obtained by calcining EFB ash at 800°C for 4 hours, followed by acid leaching with 1% HCl, dissolution in 2 M NaOH for 2 hours, and precipitation using 3 M NH?OH at 50 °C until reaching neutral pH. The resulting amorphous silica was driedand blended with biochar and 5% cassava starch binder to produceporous granules. These were enriched with Azotobacter sp. (10?CFU/g) and composted biomass as sources of slow-releasing organic NPK. Field-simulated trials in peat soils showed that the formulationraised soil pH by 0.8–1.2 units, improved CEC by up to 54%, andenhanced nutrient uptake: nitrogen by 49.7%, phosphorus by 16.2%, and potassium by 35% compared to controls. The granules maintained structural integrity under saturated conditions and released nutrientssteadily over 30–45 days, aligning with crop demand while minimizing leaching losses. This innovative, peat-specific formulation addresses key soil limitations by improving nutrient retention, buffering acidity, and introducing biological nitrogen fixation. It offers a scalable and eco-compatible solution to enhance the sustainability and productivity of palm plantations on degraded peatlands.